A novel mouse model of conditional IRAK-M deficiency in myeloid cells: application in lung Pseudomonas aeruginosa infection. Issue 2 (February 2017) - Jiang, Di; Matsuda, Jennifer; Berman, Reena; Schaefer, Niccolette; Stevenson, Connor; Gross, James; Zhang, Bicheng; Sanchez, Amelia; Li, Liwu; Chu, Hong Wei
Myeloid cells such as macrophages are critical to innate defense against infection. IL-1 receptor-associated kinase M (IRAK-M) is a negative regulator of TLR signaling during bacterial infection, but the role of myeloid cell IRAK-M in bacterial infection is unclear. Our goal was to generate a novel conditional knockout mouse model to define the role of myeloid cell IRAK-M during bacterial infection. Myeloid cell-specific IRAK-M knockout mice were generated by crossing IRAK-M floxed mice with LysM–Cre knock-in mice. The resulting LysM–Cre + /IRAK-M fl/wt and control (LysM–Cre – /IRAK-M fl/wt ) mice were intranasally infected with Pseudomonas aeruginosa (PA). IRAK-M deletion, inflammation, myeloperoxidase (MPO) activity and PA load were measured in leukocytes, bronchoalveolar lavage (BAL) fluid and lungs. PA killing assay with BAL fluid was performed to determine mechanisms of IRAK-M-mediated host defense. IRAK-M mRNA and protein levels in alveolar and lung macrophages were significantly reduced in LysM–Cre + /IRAK-M fl/wt mice compared with control mice. Following PA infection, LysM–Cre + /IRAK-M fl/wt mice have enhanced lung neutrophilic inflammation, including MPO activity, but reduced PA load. The increased lung MPO activity in LysM–Cre + /IRAK-M fl/wt mouse BAL fluid reduced PA load. Generation of IRAK-M conditional knockout mice will enable investigators to determine precisely the function of IRAK-M in myeloid cells and other types of cells during infection and inflammation.